Inﬂuence of differential spoiler settings on the wake vortex characterization and alleviation - Elsayed, Omer Ali; Asrar, Waqar; Omar, Ashraf Ali; Kwon, Kijung (American Institute of Aeronautical and Astronautic, 2010)
Experimental investigations using particle image velocimetry technique have been carried out for the evaluation of the differential spoiler setting capabilities in modifying the spanwise wing load and further reduce the wake vortex hazard. The aircraft half model (at high lift configuration) was investigated for two differential spoiler settings. Results reveal a noticeable inboard shift of spanwise wing loading. Implementation of a differential spoiler setting results in a substantial redistribution of the flap tip vortex circulation with an increase in the diameter of the merged vortex by a factor of up to 2.72 relative to the undisturbed flap tip vortex. Inspection of the cross-stream distribution of axial vorticity shows a reduction by a factor of up to 2.33 in the peak vorticity value. A 44% decrease of the maximum crossflow velocity relative to the undisturbed flap tip vortex crossflow velocity was recorded for the case of deployed spoilers. Finally assessment of the differential spoiler setting capabilities as a wake vortex attenuation device reveals that, while position of the maximum induced rolling moments in the flap tip area is little influenced by the differential spoiler setting, the maximum induced rolling moment coefficient was reduced to nearly one third of the undisturbed flap tip vortex value.